Ventricular and atrial function and deformation is largely preserved after arterial switch operation. Issue 20 (4th August 2021) - Schuwerk, Roman; Freitag-Wolf, Sandra; Krupickova, Sylvia; Gabbert, Dominik Daniel; Uebing, Anselm; Langguth, Patrick; Voges, Inga
Abstract : Objective: To test the hypothesis that ventricular and atrial function are different between patients with transposition of the great arteries (TGA) after arterial switch operation (ASO) and healthy controls. Methods: 103 consecutive patients with TGA (median age: 16.7 years, 4.3–39.6 years, 71.8% male) were compared with 77 controls (median age: 15.4 years, 6.3–43.2 years, 66.2% male). Biventricular and biatrial function were assessed using standard cardiovascular magnetic resonance (CMR) techniques and feature tracking. Group comparison was performed with conventional non-parametrical statistics and machine learning methods to find the variables most discriminative between patients and controls. These variables were used to build a multivariable logistic regression model to assess the case–control status. Results: Markers of left and right ventricular function (LV; RV) (ejection fraction, MAPSE, TAPSE, LV long-axis strain) as well as LV global longitudinal (−20.7 (−24.1; −17.9) vs −23.7 (−26.1; −21.6), p<0.001), circumferential (−29.4 (−32.2; −26.5) vs −30.5 (−33.6; 29), p=0.001) and atrial longitudinal strain (left atrium (LA): 23.3 (18.6; 28.8) vs 36.7 (30.7; 44), p<0001; right atrium: 21.7 (18.2; 27.8) vs 34.9 (26.9; 40.3), p<0.001) were reduced in patients compared with controls using non-parametrical testing. The logistic regression model including the most discriminative variables from univariate and machine learning analysis demonstrated significant differences between patients and controls only for TAPSE and LA global longitudinal strain. Conclusions: Biventricular and biatrial function are largely preserved after ASO for TGA. Using a comprehensive CMR protocol along with statistical machine learning methods and a regression approach, only RV longitudinal function and LA function are significantly impaired.